Difference sets from unions of cyclotomic classes of orders 12, 20, and 24 - Balmaceda, Jose Maria P.; Estrella, Benedict M. (Vol. 150, No. 6B (December 2021) pages 1803-1810.)
"Let q be a prime of the form q = nN + 1 for integers n ≥ 1 and N > 1. For q < 10^5, we show that difference sets in the additive group of the field GF(q) are obtained from unions of cyclotomic classes of orders N = 12, 20, and 24 and determine all such unions using a computer search. We then determine if the difference sets are equivalent to known cyclotomic or modified cyclotomic quadratic, quartic, sextic, or octic difference sets or their complements." - Title page.